Tumor Seeding after Percutaneous Transthoracic Needle Biopsy of Metastatic Pulmonary Ameloblastoma - Park, Hye Mi; Kim, Yun Hyeon; Lim, Hyo Soon; Ki, So Yeon; Lee, Hyo-jae; Lee, Jong Eun; Jeong, Won Gi (Journal of the Korean Society of Radiology, 2021)
Percutaneous transthoracic needle biopsy (PTNB) is a minimally-invasive procedure that is an indispensable tool for evaluating pulmonary lesions. Though extremely rare, tumor seeding of the pleura and chest wall can occur as a complication. Given that the breast is located anterior to the thorax, needle tracking through the breast is inevitable when PTNB is performed using the anterior approach. We describe tumor seeding of metastatic pulmonary ameloblastoma in the pectoralis muscle layer of the breast along the needle track of PTNB in a 51-year-old female presenting with a palpable lump in the right breast.